Peningkatan fungsional bedak dayak dengan ekstrak daun sirih hutan gambut Kalimantan Tengah (Piper aduncum) sebagai anti dengue - Rahman, Sudarman; Febrianto, Yahya; Fatiqin, Awalul; Sulistia, Tiya; Alfanaar, Rokiy; Arsana, Mu'afa Purwa; Suprayogi, Thathit; Desindria, Galang Rizdho; Citrariana, Shesanthi (Poltekkes Kemenkes Aceh, 2025)
Background: Dengue Hemorrhagic Fever (DHF) was disease caused by a virustransmitted the Aedes aegypti. One of the products with local wisdom that prevented DHF was the formulation of dayak powder from sirih hutan leaves. Based on phytochemical, contained terpenoids and flavonoids.Objectives: This study aims to identifythe group of antidengue compounds, determine the formula and evaluate the preparation of topical formulation.Methods: The research design used a pre experimentaldesign with variations and formula development, was conducted at the Biomedical Laboratory FK and PPIIG UPR in August-November 2024. Ethanol extract was obtained using the maceration for 3x24 hours, evaporated using a rotary evaporator and contained 132,5059 g. The extract was analyzed using GC-MS, then formulated with dayak powder and a physical test. Data were analyzed using the One Way Anova statistical test and continued Tukey's post hoc at 95% CI.Results: Sample showed 52 peak areas representing 7 possible identified compounds with a percentage of similarity> 70% (GC-MS). Then the five formulas were physically tested. The results of organoleptic and pH all formulas produced powder aromatic, green, and the criteria of skin pH range (4,5-6,5). The 5th formula showed better results based on the flow time test (5,46 seconds), the settling test produced 3,5-6% (<10%), adhesion test, smoothness, and hedonic. Based on data analysis with One Way Anova, a significant difference was produced in each dayak powder formula (pvalue=0,05).Conclusion: Ethanol extract of sirih hutan leaves has 7 possible compounds with antidengue activity and the 5th formula has better physical test results.